ANALISIS KOSAKATA DALAM KOLOM KOMENTAR INSTAGRAM AKUN JAKARTA KERAS PADA UNGGAHAN ”PEREMPUAN INI MERAYAKAN ULANG TAHUNNYA SENDIRI” - Fauziyah, Dwita Hasna; Isriyadi, Dwi Febrianti; Allfizyah, Siti; Kirana, Nanda Zahra; Muasomah; Mukhlis, Abdul (CV. Kalimasada Group, 2025)
The purpose of this study was to examine the use of vocabulary in the comments column on the upload titled “This Woman celebrates her own birthday” on The Jakarta Keras Instagram account. The approach used is descriptive qualitative with data obtained through the collection of comments from internet users. The Data is then grouped according to the type of vocabulary, such as abbreviations, decapitations, contractions and acronyms. Analyses were conducted to explore lexical and semantic aspects in a digital context. The results showed that the vocabulary in the comments serves not only as a means of communication, but also hints at the views, feelings and stereotypes that develop in society. There is a tension between moral values, empathy, humor and the form of verbal violence reflected in the comments. The choice of words used by internet users reflects a collective identity as well as a particular social position, while showing the relationship between online community norms and freedom of expression. The study highlights the importance of vocabulary analysis in social media as a way to understand the communication patterns of digital society. It is hoped that these findings can deepen the study of social linguistics, pragmatics, and digital media, as well as provide a broader understanding of the use of language in online interactions. In addition, this research could serve as a basis for the development of digital literacy that is more sensitive to language ethics and the impact of communication in virtual public spaces.